2015
DOI: 10.1111/jfb.12690
|View full text |Cite
|
Sign up to set email alerts
|

Steelhead trout Oncorhynchus mykiss metabolic rate is affected by dietary Aloe vera inclusion but not by mounting an immune response against formalin‐killed Aeromonas salmonicida

Abstract: The oxygen consumption (MO2) of two groups of 10° C acclimated steelhead trout Oncorhynchus mykiss was measured for 72 h after they were given a 100 µl kg(-1) intraperitoneal injection of formalin-killed Aeromonas salmonicida (ASAL) or phosphate-buffered saline (PBS). In addition, plasma cortisol levels were measured in fish from both groups prior to, and 1 and 3 h after, they were given a 30 s net stress. The first group was fed an unaltered commercial diet for 4 weeks, whereas the second group was fed the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…This event contributed to energy conservation, increased feed efficiency and consequently enhanced growth. Although the relationship of metabolic cost to mounting an immune response is not clear (see Zanuzzo et al [19]), BG02 also exhibited lower immunostimulation compared with BG01, suggesting more energy for growth. Furthermore, fish fed with BG02 showed increased plasma glucose levels after bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…This event contributed to energy conservation, increased feed efficiency and consequently enhanced growth. Although the relationship of metabolic cost to mounting an immune response is not clear (see Zanuzzo et al [19]), BG02 also exhibited lower immunostimulation compared with BG01, suggesting more energy for growth. Furthermore, fish fed with BG02 showed increased plasma glucose levels after bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…At present, we do not have an explanation for this result. Zanuzzo et al [53] showed that steelhead trout (Oncorhynchus mykiss) fed with 0.5% A. vera during 8 weeks had resting cortisol levels one-half of those of the control fish. Tilapia (Oreochromis niloticus) fed with A. vera diets during 60 days also had significantly difference in cortisol level compare to control fish [39].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as mounting an immune response could be costly (see [66] for discussion) the dietary composition should be monitored carefully and adapted if necessary.…”
Section: Accepted Manuscriptmentioning
confidence: 99%